An Anti-Racist reading of the notion of 'fundamental British values' - Ümit Yıldız (PRISM)
The 2020 Black Lives Matter protests were a reminder that structural racism (Sivanandan, 2008) remains prevalent at every level within British society.  The movement to decolonise the curriculum has gained momentum amongst educators and students, in recognition that the education system is one of the means by which racism is reproduced. The compulsory promotion of the notion of ‘fundamental British values (FBVs)’ is a mechanism within this production line. ‘FBVs’ play a dual role, firstly as a tool to identify the signs of ‘radicalisation’ and ‘extremism’ amongst young, predominantly Muslim people. Secondly, it acts as an assimilationist, racist educational policy which promotes the superiority of ‘British values’ over covertly identified ‘Other’ values.  This paper argues that opposing the promotion of ‘FBVs’ is an integral part of decolonising the curriculum and anti-racist schooling.